The minimalist program - Chomsky, Noam; Lasnik, Howard (Cambridge, Massachusetts : The MIT Press, 2015)
In his foundational book published in 1995, the author offered a significant contribution to the generative tradition in linguistics. This twentieth-anniversary edition reissues this classic work with a new preface by the author. The author attempts to situate linguistic theory in the broader cognitive sciences, with the chapters formulating and progressively developing the minimalist approach to linguistic theory.
The theory of principles and parameters with Howard Lasnik -- Some notes on economy of derivation and representation -- A minimalist program for linguistic theory -- Categories and transformations.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Minimalist theory (Linguistics); Minimalisme (Linguistique); LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Historical & Comparative; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Minimalist theory (Linguistics); LINGUISTICS & LANGUAGE/General